PENGGUNAAN PASIR GALIAN (MATERIAL LOKAL) DI KABUPATEN MERAUKE – PAPUA SEBAGAI KOMPONEN PENYUSUN MORTAR - Larson, Stanley (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021, 2021)
One of the infrastructure developments by the Indonesian government is in Merauke Regency. However, the availability of high-quality materials must be imported from outside, which results in high prices and long delivery times. Alternative construction materials continue to be sought and developed, such as the use of local materials. The aim of this research is to determine which sand is the best as mortar mixture. This mortar study used 3 (three) sands from quarries in Merauke, namely Onggari-1, Bupul-5, and Senayu. The ratio of mortar constituent between cement and sand is 1:2 with FAS 0.4, with 5x5x5 cm test object. The properties of each sand tested in original condition while the mortar compressive strength test was carried out at the age of 8 days, 14 days and 28 days. The mortar also will be tested for volume weight, specific gravity, and water absorption. The analysis results showed Onggari-1 met most of all the properties specifications for concrete with clay particles less than 5%, low organic impurities, and well-graded. The compressive strength achieved by Onggari-1 was the highest at 38,45 MPa, followed by Senayu at 26,01 MPa and Bupul-5 at 19,44 MPa at the age of 28 days. The highest increase in quality of each sand occurred at the age of 14 days. Sand from Senayu and Bupul-5 need maintenance in the form of washing the sand and repairing the gradation. Overall, all sands can be used as masonry work that bear large loads such as exterior and interior walls.